Effect of DHEA and metformin on corpus luteum in mice - Sander, Valeria Analía (2009)
Effect of DHEA and metformin on corpus luteum in mice Abstract We evaluated the effect of hyperandrogenism in ovaries with functional and regressing corpora lutea (CL) and the action of metformin in preventing these possible alterations using a mouse model. To obtain a CL functional for 9+/-1 days, immature female mice of the BALB/c strain were injected i.p. with 10 IU/mouse of pregnant mare´s serum gonadotropin (PMSG). DHEA (60 mg/kg body weight s.c., 24 and 48 h prior to kill) decreased both serum progesterone (P) and estradiol (E(2)) levels and increased the activity of superoxide dismutase (SOD) from ovaries with functional CL (on day 5 after PMSG). It increased P and E(2) and the activities of SOD and catalase (CAT) and decreased lipoperoxidation of ovaries with regressing CL (on day 9 after PMSG). Treatment with DHEA did not affect the production of prostaglandin F(2alpha) (PGF(2alpha)) or PGE by ovaries with functional CL, whereas DHEA decreased PGF(2alpha) and increased PGE production by ovaries with regressing CL. Metformin (50 mg/kg body weight, orally) given together with DHEA restored E(2) levels from mice with ovaries with functional CL and serum P, PGF(2alpha) and PGE levels, and oxidative balance in mice with ovaries with regressing CL. Metformin alone was able to modulate serum P and E(2) levels, lipoperoxidation, SOD and CAT, and the 5,5-dimethyl-1-pyrroline N-oxide/(*)OH signal. These findings suggest that hyperandrogenism is able to induce or to rescue CL from luteolysis and metformin treatment is able to prevent these effects.